Enzyme replacement therapy and intraepidermal innervation density in Fabry disease - Schiffmann, Raphael; Hauer, Peter; Freeman, Barbara; Ries, Markus; Scott, Leland J. C.; Polydefkis, Michael; Brady, Roscoe O.; McArthur, Justin C.; Wagner, Kathryn (Muscle & nerve, 2006)
We prospectively evaluated the effect of enzyme replacement therapy (ERT) on the intraepidermal nerve fiber density (IENFD) and thermal threshold in patients with Fabry disease, an X-linked disorder associated with a painful small-fiber neuropathy and decreased linear IENFD in a length-dependent pattern. Twenty-five hemizygous male patients with Fabry disease were enrolled in a 6-month, randomized, placebo-controlled ERT trial of 0.2 mg/kg of α-galactosidase A (agalsidase-alfa) every 2 weeks followed by an additional 12 months of open-label ERT for both populations. IENFD and thermal threshold were measured in the distal thigh at baseline, 6 months, and 18 months from initiation of the trial. We found no significant difference in IENFD between the treatment groups at 6 months. After an additional year of ERT, there was a significant reduction in IENFD in the patient group as a whole, attributable to the declining glomerular filtration rate. Thermal thresholds remained unchanged. We conclude that epidermal nerve fiber regeneration, as measured in the distal thigh, does not occur in this patient population after 12-18 months of ERT. Muscle Nerve, 2006